AKTIVITAS RION-RION PADA MASYARAKAT DESA IDAMGAMLAMO KECAMATAN SAHU TIMUR KABUPATEN HALMAHERA BARAT - Sowo, Ruben (HOLISTIK, Journal Of Social and Culture, 2017)
Help one another is joint activities to completed a a particular job considereduseful not only to public interest, but also to the benefit of specified individualsin society. Help one another this is that drives the whole system social in thelife of the Idamgamlamo village community in an activity environment hislife, among other: performs activities help one another in building a house,activities grief, and in wedding. Help one another this in community lifeidamgamlamo known rion-rion with the term, arranged with a system of â€œorowanger re fang wangerâ€ (take days) pay day. This is an authorized capital ofthe people to do the activity in various aspect of life. Rion-rion used at thetime of the community celebrating a marriage feast, died (death), build housesand another activity that deals with common interests.Through rion-rion or help one another various needs who personally theheavy for implementation, but because borne together so that is easy to beimplemented. With the togetherness in an activity rion-rion or please help thewho have their own innovation its existence, they feel all the social life couldbe met. Then to be able to meet the society necessity the various forms ofactivity help one another or rion-rion can serve as an instrument socialcontrol. Togetherness created increase heavy think alienation receivedsomeone when they are not following regulations under adat (custom ortradition). Rion-rion or help one another in the Idamgamlamo village thisthere are three (3) principle for his the principle of family spirit, the principleof cooperation, and the principle of unity.Keyword : Help one another, togetherness, rion-rion